2023
DOI: 10.17221/16/2023-pps
|View full text |Cite
|
Sign up to set email alerts
|

Ageratum yellow vein alphasatellite and tomato leaf curl Java betasatellite association with begomoviruses infecting crops and weeds in Indonesia

Adyatma Irawan Santosa,
Susamto Somowiyarjo

Abstract: The member species of the genus Begomovirus have circular single-stranded DNA genomes, which may be monopartite (having only a single genome: DNA-A) or bipartite (having two separate genomes in the same virion particle: DNA-A and DNA-B) (Fiallo-Olivé et al. 2021). Many Begomovirus species are associated with three types of satellites, namely, alpha, beta, and delta satellites, which may affect their pathogenicity and disease severity (Zhou 2013;Fiallo-Olivé et al. 2016;Zou et al. 2020). The alpha satellite gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Recent studies have shown the association of satellite molecules with begomoviruses infecting weeds in diverse regions. Weed Sinapis arvensis is a reservoir of begomoviruses and associated betasatellites in Jordan [ 60 ]; Solanum nigrum is a host of tomato leaf curl Palampur virus and CLCuMB in Pakistan [ 61 ]; Ageratum conyzoides and Amaranthus spinosus are hosts of Ageratum yellow vein China virus and tomato leaf curl Java beta satellite in Indonesia [ 62 ]; and A. conyzoides is a host of Alternanthera yellow vein virus and tomato leaf curl betasatellite in Oman [ 63 ]. Earlier studies have shown the presence of multiple and recombinant betasatellites in weeds Digera arvensis and Sonchus arvensis [ 64 , 65 ].…”
Section: Origin and Evolution Of Satellites Associated With Begomovir...mentioning
confidence: 99%
“…Recent studies have shown the association of satellite molecules with begomoviruses infecting weeds in diverse regions. Weed Sinapis arvensis is a reservoir of begomoviruses and associated betasatellites in Jordan [ 60 ]; Solanum nigrum is a host of tomato leaf curl Palampur virus and CLCuMB in Pakistan [ 61 ]; Ageratum conyzoides and Amaranthus spinosus are hosts of Ageratum yellow vein China virus and tomato leaf curl Java beta satellite in Indonesia [ 62 ]; and A. conyzoides is a host of Alternanthera yellow vein virus and tomato leaf curl betasatellite in Oman [ 63 ]. Earlier studies have shown the presence of multiple and recombinant betasatellites in weeds Digera arvensis and Sonchus arvensis [ 64 , 65 ].…”
Section: Origin and Evolution Of Satellites Associated With Begomovir...mentioning
confidence: 99%
“…Combination of bio-fertilizer was suggested for further improvement (Khairi et al, 2023) but it is actually very challenging due to other limitations. One of major constraints in the cultivation of chili pepper, tomato, and squash in the country is yellowing disease caused by begomoviruses (Santosa & Somowiyarjo, 2023;Wahyono et al, 2023). Species of Begomovirus have monopartite or bipartite single stranded DNA genomes, and transmitted by whitefly (Bemisia tabaci) and some also by seeds (Brown et al, 2015).…”
Section: Introductionmentioning
confidence: 99%